2019
DOI: 10.1016/j.jtho.2018.10.166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prognostic Significance of TNM Staging Guidelines in Lung Carcinoid Tumors

Abstract: Introduction: The TNM classification for lung cancer, originally designed for NSCLC, is applied to staging of bronchopulmonary carcinoid tumors. The validity of the eighth edition of the staging system for carcinoid tumors has not been assessed. In this study, we evaluated its prognostic accuracy by using data from a large national population-based cancer registry.Methods: Patients with typical and atypical bronchopulmonary carcinoids diagnosed between 2000 and 2013 were identified from the National Cancer Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 21 publications
(20 reference statements)
5
65
1
Order By: Relevance
“…Because of its relatively uncommon nature, no specific clinical prognostic tool exists for AC. Previous studies suggested the staging of pulmonary NETs according to the American Joint Committee on Cancer (AJCC) staging system [7]. Nonetheless, this suggestion is questionable given the very different biology, variable clinical presentation and therapeutic approaches between pulmonary ACs and other usual histological subtypes of lung cancer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its relatively uncommon nature, no specific clinical prognostic tool exists for AC. Previous studies suggested the staging of pulmonary NETs according to the American Joint Committee on Cancer (AJCC) staging system [7]. Nonetheless, this suggestion is questionable given the very different biology, variable clinical presentation and therapeutic approaches between pulmonary ACs and other usual histological subtypes of lung cancer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Union for International Cancer Control TNM classification system is one of the most common methods used by clinicians to evaluate the prognosis of patients with GC (3). However, this system has certain limitations, such as the fact that patients with the same tumor stage may have different clinical outcomes (4,5). Therefore, it is imperative to identify other independent prognostic markers for GC to further classify patients who have been staged according to the TNM system into subgroups with good and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the early and middle status, HRs did not increase with the increase of stages, or there was no difference in HRs between adjacent stages. Similar grading prognostic results for carcinoid could be seen in lung carcinoid 6 . These findings limited the usefulness of the 8th TNM staging system.…”
Section: Discussionmentioning
confidence: 58%
“…As the screening popularity of colonoscopy, colorectal carcinoids were more commonly found in the United States, with rectal carcinoids accounting for about 20% 4,5 . Because of the lack of uniform classification standards and relatively special nature, no recognized and unified staging system existed for these tumors 6 . The World Health Organization (WHO) Classification of the Digestive System 2010 used “neuroendocrine neoplasm (NEN)” to bridge this classification gap 2 .…”
Section: Introductionmentioning
confidence: 99%